THE ROLE OF UZBEK FOLK SONGS IN THE SPIRITUAL AND MORAL EDUCATION OF YOUTH (Scientific journal of the Fergana State University, 2024)
This article describes the role of Uzbek folk songs in the spiritual and moral education of youth, about the way of life, social and everyday life of the people, work activities, views, beliefs and religious ideas of the people, examples of folk art, spiritual and moral thoughts about the artistic world are expressed .